(untitled) (Academia Journal of Medicine, 2019)
Background: Over the past two decades with the advent of highly active antiretroviral therapy (HAART), there is a substantial increase in the life span of HIV patients. Hence, the focus has now shifted to managing long-term complications of HIV infection and improving the quality of life of HIV patients, especially in developed nations. On the other hand, in developing nations, the ever-growing incidence of HIV infection has placed a huge burden on their frail economy, so there is a growing need for simplifying HIV treatment protocols and for having cheaper alternatives for monitoring disease activity. Subjects and Methods: The present study was a cross sectional hospital based study for a period of twelve months from 1st Nov. 2015 to 31st Oct. 2016 at ART center P.B.M. Hospital, Bikaner. 100 HIV+ patients on ART were included in the study by consecutive sampling technique. Out of 100 patients, 50 were symptomatic and included in study group and remaining 50 were asymptomatic and taken as controls. Results: 37 (74%) patients in study group had CRP levels >6 mg/lit (normal level <6 mg/lit). Out of 37, 19 subjects (38% of total) had CRP level >20 mg/lit. While in control group, 44 subjects (88%) had CRP level <6 mg/lit. Only 6 (12%) subjects of control group had CRP level >6mg/lit. None of control subjects had CRP level >20 mg/lit. The CRP levels and CD4 count were negatively correlated in study group and this was observed to be statistically significant (p=0.04) whereas in control group, the CRP levels and CD4 counts were found to be very weakly positively correlated and this correlation was observed to be statistically insignificant. Conclusion: There was statistical significant difference between CRP range and levels in both the groups. Also statistical significant difference between CD4 count range in both the groups. In our study, 38% of the study group patients had CRP >20 mg/l whereas 88% of the control subjects had CRP of <6 mg/l.